Prevalence of Overactive Bladder Symptoms Among Women With Interstitial Cystitis/Bladder Pain Syndrome. Issue 3 (March 2022) - Dubinskaya, Alexandra; Tholemeier, Lauren N.; Erickson, Tyler; De Hoedt, Amanda M.; Barbour, Kamil E.; Kim, Jayoung; Freedland, Stephen J.; Anger, Jennifer T.
Abstract : Importance: Symptoms of urinary frequency, urgency, and urinary leakage are characteristic of overactive bladder (OAB) syndrome. However, frequency and urgency symptoms are also present in most patients with interstitial cystitis/bladder pain syndrome (IC/BPS). Objective: Our objective was to describe the urge incontinence among women with IC/BPS, which may indicate true overlap of OAB and IC/BPS. Study Design: This is a prospective study of women with IC/BPS diagnosed clinically in the Veterans Affairs Health Care system. Patients completed the OAB and Female Genitourinary Pain Index (F-GUPI) questionnaires. Questions from the OAB questionnaire were used to analyze symptoms of urinary urgency and urge incontinence. Pain symptoms, urinary symptoms, and impact on quality of life were assessed based on the F-GUPI. Patient demographics, comorbidities, and symptoms were reviewed. Results: Within the cohort of 144 women with IC/BPS, 100 (69%) had urinary leakage associated with the strong desire to void and were more likely to have incontinence compared with healthy controls ( P < 0.001). The IC/BPS group also had higher total and pain scores on the F-GUPI ( P < 0.001), but pain scores were not affected by the presence of incontinence ( P = 0.478). Conclusions: The prevalence of OAB symptoms of urinary leakage is high among women with IC/BPS. This may explain the efficacy of OAB medication and third-line therapies in this population.